Simulasi (Gosip) Infotainment dalam Retorika Image (Keaiban) Selebritis - Anicetus Windarto (Sanata Dharma University, 2023)
This study is intended to: (1) become aware of forms of celebrities’ rhetorical (im)morality which are constructed as (floating) signifiers in infotainment; (2) understand and interpret the political media minutely based on communication technology of virtual reality and/or real virtuality that is produced by forms of celebrities’ rhetorical (im)morality in infotainment; (3) reconstruct and disseminate the understanding and action of cultural paradigms based on the results of re-examination of reality and / or infotainment virtuality which inspired the idea of celebrity (im)morality. The main contribution of this study is to offer a perspective that attempts to understand, interpret, and become aware of infotainment shows through Baudrillard’s notion of simulation. This study attempts to describe the reality as that which had been created through the infotainment show by its celebrity’s rhetorical (im)morality and how ironic an impact it has in our society.